164k views
5 votes
Solve using elimination. Please explain while you're solving.

-x - 18y = -3
7x - 9y = 21

User Planben
by
8.2k points

1 Answer

4 votes
-x - 18y = -3 (equation 1)

7x - 9y = 21
14x - 18y = 42 (equation 2)

equation 1 - equation 2,
(-x - 18y) - (14x - 18y) = -3 - 42
-x - 18y - 14x + 18y = -45
-15x = -45
15x = 45
x = 3

substitute x = 3 into equation 1,
-x - 18y = -3
-(3) - 18y = -3
-3 - 18y = -3
-3 - 18y + 3 = -3 + 3
- 18y = 0
y = 0

The values of x and y is 3 and 0 respectively.

By using the elimination method, you cancel out the y term in both equations 1 and 2 by subtracting equation 1 with equation 2.
User Akos Krivachy
by
7.3k points